Case report: Virtual reality-based arm and leg cycling combined with transcutaneous electrical spinal cord stimulation for early treatment of a cervical spinal cord injured patient - Chu, Xiaolei; Liu, Shuaiyi; Zhao, Xiaoxuan; Liu, Tao; Xing, Zheng; Li, Qingwen; Li, Qi (Frontiers in Neuroscience, 2024)
Spinal cord injury is a condition affecting the central nervous system, causing different levels of dysfunction below the point of nerve damage. A 50-year-old woman suffered a neck injury as a result of a car accident. After undergoing posterior cervical C3-C6 internal fixation with titanium plates on one side and C7 lamina decompression, the patient, who had been diagnosed with C3-C7 cervical disc herniation and spinal stenosis causing persistent compression of the spinal cord, was transferred to the rehabilitation department. After implementing the combined therapy of Virtual Reality-based arm and leg cycling along with transcutaneous electrical stimulation of the spinal cord, the patients experienced a notable enhancement in both sensory and motor abilities as per the ASIA scores. The patient's anxiety and depression were reduced as measured by the Hamilton Anxiety and Hamilton Depression Tests. As evaluated by the SCIM-III, the patient's self-reliance and capacity to carry out everyday tasks showed ongoing enhancement, leading to the restoration of their functionality. Hence, the use of Virtual Reality-based arm and leg cycling along with transcutaneous electrical spinal cord stimulation has potential to positively impact function in patients with spinal cord injury. However, as this is a case report, the small number of patients and the fact that the intervention was initiated early after the injury, we were unable to separate the recovery due to the intervention from the natural recovery that is known to occur in the initial weeks and months after SCI. Therefore, further randomized controlled trials with a large sample size is necessary.